COMPARISON RESULTS OF THE INTRACARDIAC ELECTROPHYSIOLOGICAL STUDY IN PATIENTS WITH TYPICAL ATRIAL FLUTTER AND FIBRILLATION - P. S. Novikov; A. V. Pevzner; A. V. Shlevkov; E. V. Maykov; N. Yu. Mironov; S. F. Sokolov; S. P. Golitsyn (Российский кардиологический журнал)
Aim. Comparison study of the parameters of intracardiac electrophysiological study (EPS) in patients with the typical atrial flutter (TAF) and atrial fibrillation (AF), of the courses as isolated types of arrhythmia.Material and methods. Totally, 82 patients included (59 (72%) males, mean age 55±10 y.o.), directed for catheter ablation procedure for TAF or AF. Depending on the anamnesis of arrhythmia, patients were selected to 4 groups: 1 — isolated TAF (n=26, 32%), 2 — AF with “spontaneous” TAF (n=27, 33%), 3 — AF and TAF, when the latter had been registered only under treatment by antiarrhythmics of IC and III classes (n=14, 17%), 4 — isolated AF (n=15, 18%). All patients underwent EPS within sinus rhythm and no antiarrhythmic therapy. During EPS the following parameters were defined: P-wave duration, time of interand intra-atrial conduction, effective refractory periods (ERP) in various areas of the atria. By the results of EPS, comparative statistical study performed of the listed parameters in the groups.Results. Patients with TAF (groups 1, 2, 3), in difference with isolated AF (group 4) had significantly longer P-wave and inter-atrial conduction time. Analysis of ERP showed similar heterogeneity of the parameters in different areas of the atria in all studied groups: the lowest ERP is found in the lateral area of the right atrium, the highest — in the distal area of coronary sinus. Intergroup differences by these parameters were non-significant.Conclusion. For TAF patients, as an isolated disorder or with AF, the characteristical is significant prolongation of the inter-atrial conduction time, that might expain tendency to tachiarrhythmias of re-entry genesis.